Seasonal Variation of Physico-Chemical Characteristics of Water in Two Wetlands of Tiptur Taluk, Karnataka - Raghavendra Gowda, H.T., and Pramod, A. F., Jagadeshappa, K .C1., Vijaya Kumara* (Recent Research in Science and Technology, 2011)
<div style="border-bottom: windowtext 1pt solid; border-left: medium none; padding-bottom: 1pt; padding-left: 0in; padding-right: 0in; margin-left: 34pt; border-top: medium none; margin-right: 34pt; border-right: medium none; padding-top: 0in; mso-element: para-border-div; mso-border-bottom-alt: solid windowtext .5pt;"> The present study was carried out to evaluate the physico-chemical parameters of Sugur and Bajagur wetlands, located at Tiptur taluk, of Tumkur district, Karnataka. The physicochemical parameters play a vital role in the wetland ecosystems. A significant variation in these parameters was observed throughout the study period and monthly comparisons were made as monsoon, pre-monsoon and post-monsoon. The results of the present investigations are compared with literature values and investigation reveals that there is a fluctuation in the physico-chemical characters of the water this will be due to in flow and change in the temperature as season changes